Role of Energy Exchanges for Power Trading in India - Girish, G. P.; Vijayalakshmi, S. (International Journal of Energy Economics and Policy, 2015)
The Indian Electricity Act 2003 defines power trading as "The Purchase of electricity for resale thereof". In this study, we review various facets of power trading, Indian electricity market, power exchanges and the day-ahead spot electricity market of India. The power exchanges are attributed with inherent features like being nationwide, ensuring anonymity, offering transparency, being automated and enabling efficient price-discovery, we believe that, power trading in India is all set to undergo a paradigm shift in terms of volume of transaction through power exchanges, price discovery, number of participants and will eventually ensure in playing a major role in addressing the biggest concern of supply-demand mismatch of electricity in India. Keywords: Power Trading; Energy Exchanges; Indian Electricity Market JEL Classifications: C01; C22; C53